Using the ICH estimand framework to improve the interpretation of treatment effects in internet interventions - Manuel Heinrich; Pavle Zagorscak; Johannes Bohn; Christine Knaevelsrud; Lars Schulze (npj Digital Medicine)
Abstract The ICH E9(R1) Addendum on Estimands and Sensitivity Analysis provides a framework for defining the treatment effect a trial intends to estimate—the estimand. The addendum is widely adopted in pharmaceutical research. However, it remains underutilized in trials investigating internet-based interventions (IBIs). This manuscript introduces the addendum to IBI researchers. It concludes that estimands are essential to improve the interpretability, relevance, and validity of effect estimates derived in IBI trials.